Trees of Tales: Designing Playful Interactions to Enhance Reading Experiences - Al Aamri, F.; Greuter, S.; Walz, Steffen (2016)
The inclusion of interactive content has become commonplace in many reading applications for children. However, a growing body of research suggests that the inclusion of interactive content that is not tightly integrated into the narrative of the story may distract the attention of young children from the story's content and their understanding of the text and therefore requires careful consideration. This paper discusses the design of an interactive reading app for Omani children called Trees of Tales, which utilised a Mise en scène inspired game mechanic to facilitate playful and content related engagement with the e-book's narrative. We tested the reading app with 18 Omani children and their parents and compared it to printed storybooks and e-books with limited interactivity. Our study suggests that the Mise en scène approach in Trees of Tales enhanced the reading experiences of the children and motivated them to read more in the future.